Impact of an inquiry unit on grade 4 students' science learning - Di Mauro, Florencia (2016)
This paper concerns the identification of teaching strategies that enhance the development of 4th grade students’ experimental design skills at a public primary school in Argentina. Students’ performance in the design of relevant experiments was evaluated before and after an eight-week intervention compared to a control group, as well as the persistence of this learning after eight months. The study involved a quasi-experimental longitudinal study with pre-test/post-test/delayed post-test measures, complemented with semi-structured interviews with randomly selected students. Our findings showed improvement in the experimental design skills as well as its sustainability among students working with the inquiry-based sequence. After the intervention, students were able to establish valid comparisons, propose pertinent designs and identify variables that should remain constant. Contrarily, students in the control group showed no improvement and continued to solve the posed problems based on prior beliefs. In summary, this paper shows evidence that implementing inquiry-based units involving problems set in cross-domain everyday situations that combine independent student work with teacher guidance significantly improves the development of scientific skills in real classroom contexts.